Students’ Responses To The Implementation of Paragraph Shrinking Strategy in Improving Reading Comprehension - Zurina Zora; Tri Putri Utami (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
This research aimed to find out students’ responses to the activities presented in the classroom after the implementation of Paragraph Shrinking Strategy to improve reading comprehension. This research was carried out to the first grade students in one of junior high school in Aceh. The data collected by questionnaire, then tabulated in Microsoft Excel and analyzed descriptively. The results showed that students’ responses to the implementation of Paragraph Shrinking Strategy were positive, as Paragraph Shrinking Strategy is effective in improving reading comprehension.